Peningkatan Kompetensi Kewirausahaan Siswa SMK Melalui Pelatihan Penyusunan Business Model Canvas Berbasis Digital - Elvi Rahmi; Efni Cerya; Friyatmi Friyatmi (Jurnal Ecogen, 2020)
This article aims to describe how the entrepreneurial competence of vocational school students after being given training in compiling a business plan using the Business Model Canvas. The Business Model Canvas is a comprehensive yet practical business model. This article uses a descriptive method, because this research is not intended to test certain hypotheses but only describes "what is" about the conditions to be studied, the research was conducted at SMKN 1 Baso. Data were collected using a questionnaire from 28 respondents. From the research results it is known that there is an increase in understanding, skills and insights of students in entrepreneurship, especially in making business plans using the business model canvas